Republic of Azerbaijan : Climate Change and Agriculture Country Note - World Bank (World Bank, Washington, DC, 2015)
This country note for Azerbaijan is part of a series of country briefs that summarize information relevant to climate change and agriculture for three countries in the Southern Caucasus Region, with a particular focus on climate and crop projections, adaptation and mitigation options, policy development and institutional involvement. The note series has been developed to provide a baseline of knowledge on climate change and agriculture for the countries participating in the regional program on reducing vulnerability to climate change in Southern Caucasus agricultural systems. This note for Azerbaijan was shared with the Government and other agricultural sector stakeholders and used as an engagement tool for a National Awareness Raising and Consultation Workshop, held in Baku in March 2012. Feedback and comments on the note from this consultation process have been incorporated into this updated version in collaboration with the Azerbaijan Ministry of Agriculture.